Analysing the opinions of provincial directors of youth services and sports regarding the formation of modern sports awareness in Turkey - Yücel, Ali Serdar (My University, 2015)
The purpose of this study is to determine the opinions of the provincial directors working in Provincial Directorate of Youth Services and Sports serving in 81 cities of Turkey regarding the formation of modern sports awareness in Turkey. The population of the research is composed of Provincial Directors working in 81 cities of Turkey. The sample is composed of 67 Provincial Directors selected using random sampling method. In this applied research, 5 Likert Type Scale were implemented. Following the study, it has been concluded in line with the participants’ opinions that modern sports awareness has not been formed in Turkey; and there is a need for institutionalization, adequate club activities, more effective local administration, a functional sports policy and creating modern sports legislation. A significant difference was found on age and service period according to the participants’ opinions, no significant difference was determined on education and place of duty.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Sport management; Sports culture; Sports policy; Institutionalization; Sports legislation